Formal controls, neighborhood disadvantage, and violent crime in U.S. cities: Examining (un)intended consequences. (March 2016) - Martin, Allison; Wright, Emily M.; Steiner, Benjamin
Abstract: Purpose: This study examines the intended and unintended effects of formal social controls on violent crime within and across U.S. cities. Methods: Using data from the National Neighborhood Crime Study, we assess whether greater police arrest activity and jail incarceration risk are associated with lower violent crime rates across cities. We also investigate whether greater use of these formal social controls exacerbates the relationship between extreme neighborhood disadvantage and violent crime. Results: Results from multilevel analyses show that some formal controls (jail incarceration risk) reduce violent crime across cities, but other formal controls (police arrest activity) amplify the relationship between extreme neighborhood disadvantage and violent crime within cities. Conclusions: Two main conclusions can be drawn from our analyses. First, we found evidence that some formal controls do reduce violent crime, while others do not. Second, our results support scholars' arguments that formal controls have unintended consequences (e.g., Clear, 2007, 2008; Rose & Clear, 1998), specifically, by amplifying the effect of extreme neighborhood disadvantage on violent crime. Highlights: Some formal controls (jail incarceration risk) reduce violent crime across cities. Some formal controls (police arrest activity) amplify the relationship between extreme neighborhood disadvantage and violent crime within cities. Structural characteristics of neighborhoods (e.g., disadvantage, residential instability) and cities (black isolation) affect violent crime within and across cities.